Kajian Equine Infectious Anemia pada Kuda Impor di Bandar Udara Internasional Soekarno-Hatta - Marlefzena Marlefzena; Sri Murtini; Joko Pamungkas (Jurnal Sain Veteriner, 2018)
Equine Infectious Anemia (EIA) disease is caused by EIA Virus (EIAV) from genus Lentivirus, subfamily Orthoretrovirinae, family retroviridae. This virus causes a persistent infection and potentially fatal in Equidae. There is no scientific literature yet for this disease in Indonesia. In order to determine this disease in our country, it is necessary continuing laboratory detection in imported Equidae and conducted further surveillance in Equidae throughout Indonesia. This research is aimed (1) to detect of any antibodi titre of EIAV in imported horse, (2) To get information about the relationship between laboratory result with the secondary datas of origin country. The EIAV antibody detected by indirect enzyme-linked immunosorbent assay (indirect ELISA). The secondary datas were collected from Health Certificate of origin country, World Animal Health Information System (WAHIS) Interface OIE and literatures. Total of 133 blood samples were collected from imported horse, ex-imported horse and lokal breed horse. The result showed that all of imported horse, ex-imported horse and lokal breed horse were negative antibody against EIAV. The initial information on Equine Infectious Anemia indicated that health requirement in imported horse has fulfilled, so that imported horse was free from EIAV.